Studi Perbandingan Variasi ph Buffer Fosfat Pada Kualitas Pewarnaan Giemsa Terhadap Hitung Jenis Leukosit - Hesty Aulya Putri; Anisa Solikhati (Poltekkes Kemenkes Semarang, 2026)
Blood is an important fluid in the body that functions to circulate nutrients, carry metabolic waste, and play a role in the body's defense system. Leukocytes, especially neutrophils and lymphocytes, are white blood cells that play a major role in the immune response. One of the hematology tests often performed to assess the morphology and percentage of leukocytes is the examination of peripheral blood smears with Giemsa staining. The quality of Giemsa staining results is influenced by the pH of the phosphate buffer, because a pH that is too acidic or alkaline can cause the color of the nucleus and cytoplasm of cells to become unclear. This study aims to determine the effect of differences in phosphate buffer pH on the quality of Giemsa staining in leukocyte differential count examinations. This study used a quasi-experimental design with a quantitative approach and was conducted in January 2025 at the Medical Laboratory Technology Laboratory of the Muhammadiyah University of Kudus. The independent variable was the pH of the phosphate buffer with variations of pH 4, 7, and 8, while the dependent variable was the quality of Giemsa staining on leukocyte differential counts. The research sample consisted of 9 final year students selected using random sampling technique, with each sample receiving three different phosphate buffer pH treatments. Data analysis was performed using the Kruskal-Wallis test because the data were not normally distributed and showed significant differences between pH groups. Further Mann-Whitney tests showed significant differences between pH 7 and pH 8 groups. The results indicate that variations in phosphate buffer pH affect the quality of Giemsa staining and leukocyte count accuracy.